EFFECTS OF AN AQUATIC PHYSICAL THERAPY INTERVENTION IN PATIENTS AFTER STROKE - Tonieto, Maira; Rama, Priscila; Schuster, Rodrigo Costa; Renosto, Alexandra (Journal of Health Care, 2015)
Introduction: The stroke is caused by the obstruction or rupture of one or more arteries causing lack ofblood circulation in the brain. As consequences there are motor injuries, sensory, cognitive, communicativeand emotional. Objectives: Analyze the effects of an aquatic physiotherapy intervention in stroke patients.Materials and Methods: Six patients with a diagnosis of stroke were selected and submitted to 18 sessionsof aquatic therapy. The evaluation was done before and after the intervention with the questionnaireStroke Specific Quality of Life Scale (SS-QOL) to assess the quality of life, the Test of 6-minute walk,to assess the functional capacity and the Walk Test of 10 meters to measure gait speed. Results: Sixpatients participated in the study with an average age of 58.7 Â± 7.7 years, average time after stroke of 5.7Â± 4.2 years. Significant values were obtained in all variables. Quality of life (SS-QOL) average was 163points in pre-intervention and in post-intervention in 185.7. The 10-meter walk test (10MWT) averagewas 25 seconds in pre-intervention, and in post-intervention was 13 seconds. The 6-minute walk test(6MWT) average was 214.7 meters in distance pre-intervention, and post-intervention was 161 meters.Conclusions: Aquatic physical therapy protocol applied in post-stroke patients resulted in an increase inquality of life, gait speed, and functional capacity of these individuals.
Keywords: Stroke; hydrotherapy; rehabilitation